Longitudinal Stability of Common TMJ Structural Disorders - Schiffman, E L; Ahmad, M; Hollender, L; Kartha, K; Ohrbach, R; Truelove, E L; Zhang, L; Hodges, J S; Sommers, E; Anderson, G C; Gonzalez, Y M; Guo, X; et al. (Journal of dental research, 2017)
The longitudinal course of temporomandibular joint (TMJ) disc displacement (DD) and degenerative joint disease (DJD) has never been conclusively described with magnetic resonance imaging and computed tomography, respectively. This 8-y observational study's objective was to assess the longitudinal stability of DD and DJD among 401 subjects. The Validation Project provided baseline measures; follow-up was performed in the TMJ Impact Project. With magnetic resonance imaging, 2 radiologists rendered a consensus diagnosis of normal/indeterminate, DD with reduction, or DD without reduction. Computed tomography consensus diagnoses included normal/indeterminate, grade 1 DJD, or grade 2 DJD. Radiologist reliability was assessed by kappa; a Hui-Walter model was used to estimate, after accounting for diagnostic disagreement, the frequency of diagnostic progression and reversal. Permutation tests were used to test the statistical influence of concurrent baseline diagnoses on diagnostic changes at follow-up. Of 789 baseline joint-specific soft tissue diagnoses of DD, 598 (76%) joints showed no change; 109 (14%) demonstrated progression; and 82 (10%) had reversal. Of 794 joints with baseline joint-specific hard tissue diagnoses of DJD, progression was observed in 122 (15%) joints, no change in 564 (71%), and reversal in 108 (14%). Radiologist reliability (kappa) was 0.73 (95% CI, 0.64 to 0.83) for DD and 0.76 (95% CI, 0.68 to 0.83) for DJD. After accounting for the influence of diagnostic disagreement, progression of hard tissue diagnoses in the right TMJ occurred in 15.2% of subjects (95% CI, 10.5% to 20.8%) and reversal in 8.3% (95% CI, 4.9% to 12.3%); results were similar for soft tissue diagnoses and the left TMJ. Concurrent baseline soft tissue diagnoses were associated with hard tissue diagnostic changes at follow-up ( P < 0.0001). Baseline hard tissue diagnoses showed no statistical association with soft tissue changes at follow-up ( P = 0.11). Longitudinally, 76% of baseline TMJ soft tissue diagnoses and 71% of the baseline hard tissue diagnoses remained stable. Diagnostic reversal and progression were confirmed for both soft and hard tissues.